Meningkatkan Hasil Belajar Siswa Pada Materi Ikatan Kimia Dengan Model Pembelajaran Berbasis Masalah - Indeng Ratna Sari; Yuniati Tewa; Muh. Alim marhadi (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2023)
The purpose of this study was to determine the increase in student learning outcomes by applying a problem-based learning model to chemical bonding material. The sample in this study were 32 students of class X IPA 1 at SMAN 10 Kendari. The research method used was Pre-Experimental with the research design One-group Pre-test Post-test Design. Data collection in this study used research instruments in the form of learning achievement test questions, observation sheets of student and teacher activities, as well as student response questionnaires to the application of problem-based learning models. Based on the results of the study, it was found that the problem-based learning model could improve student learning outcomes in the subject matter of chemical bonds in class X ipa 1 at SMAN 10 Kendari with an N-gain value of 0.76 and included in the high category and an average student response of 78 .90%. As well as achieving the success criteria in the form of mastery learning standards on the subject matter of chemical bonds as many as 24 students or 81.25% with learning outcomes ≥70.